Calcium montmorillonite clay reduces AFB1 and FB1 biomarkers in rats exposed to single and co‐exposures of aflatoxin and fumonisin. Issue 7 (6th November 2013) - Mitchell, Nicole J.; Xue, Kathy S.; Lin, Shuhan; Marroquin‐Cardona, Alicia; Brown, Kristal A.; Elmore, Sarah E.; Tang, Lili; Romoser, Amelia; Gelderblom, Wentzel C. A.; Wang, Jia‐Sheng; Phillips, Timothy D.
ABSTRACT Aflatoxins (AFs) and fumonisins (FBs) can co‐contaminate foodstuffs and have been associated with hepatocellular and esophageal carcinomas in humans at high risk for exposure. One strategy to reduce exposure (and toxicity) from contaminated foodstuffs is the dietary inclusion of a montmorillonite clay (UPSN) that binds AFs and FBs in the gastrointestinal tract. In this study, the binding capacity of UPSN was evaluated for AFB1, FB1 and a combination thereof in Fischer 344 rats. Rats were pre‐treated with different dietary levels of UPSN (0.25% or 2%) for 1 week. Rats were gavaged with a single dose of either 0.125 mg AFB1 or 25 mg FB1 per kg body weight and a combination thereof in the presence and absence of an aqueous solution of UPSN. The kinetics of mycotoxin excretion were monitored by analyzing serum AFB1‐albumin, urinary AF (AFM1) and FB1 biomarkers over a period of 72 h. UPSN decreased AFM1 excretion by 88–97%, indicating highly effective binding. FB1 excretion was reduced, to a lesser extent, ranging from 45% to 85%. When in combination, both AFB1 and FB1 binding occurred, but capacity was decreased by almost half. In the absence of UPSN, the combined AFB1 and FB1 treatment decreased the urinary biomarkers by 67% and 45% respectively, but increased levels of AFB1‐albumin, presumably by modulating its cytochrome metabolism. UPSN significantly reduced bioavailability of both AFB1 and FB1 when in combination; suggesting that it can be utilized to reduce levels below their respective thresholds for affecting adverse biological effects. Copyright © 2013 John Wiley & Sons, Ltd.